Wind Power Forecasting For The Province Of Osmaniye Using Artificial Neural Network Method - YANIKTEPE, BULENT; TASDEMIR, SAKIR; GUHER, A. BURAK; AKCAN, Sultan (Prof. Dr. Ismail SARITAS, 2016)
Although wind energy at certain intervals and random in nature, today it is one of the commonly utilized alternative energy source in the world. Because of sustainability and environmentally-friendly energy source, countries increasingly benefit from wind energy. Several estimation methods are applied in the determination of a regions wind energy potential. Today, one of the most commonly used prediction methods is artificial neural network (ANN) method. In this study, Estimation of wind power in Osmaniye district was investigated in method with artificial neural network (ANN) using data from meteorological measurement stations from the meteorological measurement device at the campus of Osmaniye Korkut ATA University. In order to give the best values of prediction results, several methods increasing the impact on output of different models for the input variables were investigated.Ã‚Â